Redox/enzyme sensitive chondroitin sulfate-based self-assembled nanoparticles loading docetaxel for the inhibition of metastasis and growth of melanoma. (15th March 2018) - Liu, Mengrui; Du, Hongliang; Khan, Abdur Rauf; Ji, Jianbo; Yu, Aihua; Zhai, Guangxi
Highlights: Novel chondroitin sulfate-ss-deoxycholic acid (CSCD) conjugates were initially synthesized. CSCD could self-assemble to intelligent nanoparticles with redox/enzyme responsiveness. Enzyme responsive property was initially proposed in our paper for facilitating drug release. In vitro and in vivo evaluation including anticancer and antimetastasis abilities were assessed. Abstract: In this report, redox/enzyme responsive chondroitin sulfate-ss-deoxycholic acid (CSCD) conjugates were synthesized using cystamine as the linkage which could self-assemble to form self-assembled nanoparticles (175.6 +  5.2 nm) in the aqueous environment. Docetaxel (DTX) was loaded in nanoparticles with desired loading efficiency for the inhibition of tumor growth and metastasis of melanoma. Interestingly, nanoparticles were demonstrated to respond to hyaluronidase-1 (Hyal-1) which could degrade chondroitin sulfate (CS) backbones. In this case, we designed dual-sensitive nanoparticles with enhanced drug release pattern under the presence of glutathione (GSH)/Hyal-1. Compared with Taxotere®, CSCD nanoparticles significantly improved the DTX distribution in tumors and lungs with about 4.4-fold higher area-under-the-curve (AUC) value. In situ tumor volume and pulmonary metastatic formation were reduced upon the administration of DTX-loaded CSCD nanoparticles via DTX-induced apoptosis and decreased metastasis-promotion protein expression. With only minor cytotoxicity, CSCD nanoparticles could be promising nano-drug delivery systems for successful management of melanoma.